Making sorghum 'pop'ular - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Almost all sorghum varieties pop when heated briefly in cooking oil, and can be eaten as a salty snack. 'Sorghum is readily available and healthier than the popcorn we buy at silly prices,' says Professor Babatunde Obilana, a sorghum breeder in...